Pregaming on alcohol products among male college students in puducherry-mixed-methods study - Divya Rajaseharan; Amol R Dongre (Wolters Kluwer Medknow Publications, 2021)
Background: There are some risky practices such as preloading or pregaming which exist among college students. When students pregame, compared with drinking episodes when they do not, they consume a greater number of drinks and have higher blood alcohol concentrations. Objectives: (1) To explore the perceptions about pregaming among male college students in Puducherry. (2) To study the prevalence of pregaming among current alcohol users. Materials and Methods: A sequential exploratory mixed-method study (Qualitative-Focus Group Discussion [FGD] to explore pregaming followed by Quantitative-self-administered questionnaire [survey]) was conducted among 450 male engineering college students by simple random sampling. Results: The prevalence of pregaming among current alcohol users was 66.7%. Among all occasions, the students were involved in pregaming mostly on birthdays 92.5% and marriages 92.5% followed by college cultural events 90%. All of the students 100% wanted to pregame for anticipated alcohol cost problems, 100% pregamed for fun and 87.5% easy conversations with the opposite sex and majority 66.6% had the intention to quit pregaming among current users. Conclusion: The prevalence of pregaming is high among current users however, the majority of them had the intention to quit this behavior. Counselors and health care professionals working in alcohol de-addiction centers should specifically question pregaming and its associated symptoms. Tailor-made interventions should be promoted to target the concept of pregaming-related consequences of alcohol addiction.